Nature of radio feature formed by re‐started jet activity in 3C 84 and its relation with γ ‐ray emissions. Issue 1 (February 2016) - Nagai, H.; Chida, H.; Kino, M.; Orienti, M.; D'Ammando, F.; Giovannini, G.; Hiura, K.
Abstract: Re‐started jet activity occurred in the bright nearby radio source 3C 84 in about 2005. The re‐started jet is forming a prominent component (namely C3) at the tip of jet. The component has showed an increase in radio flux density for more than 7 years while the radio spectrum remains optically thin. This suggests that the component is the head of a radio lobe including a hotspot where the particle acceleration occurs. Thus, 3C 84 is a unique laboratory to study the physical properties at the very early stage of radio source evolution. Another important aspect is that high energy and very high energy γ ‐ray emissions are detected from this source. The quest for the site of γ ‐ray emission is quite important to obtain a better understanding of γ ‐ray emission mechanisms in radio galaxies. In this paper, we review the observational results from very long baseline interferometry (VLBI) monitoring of 3C 84 reported in series of our previous papers. We argue the nature of re‐started jet/radio lobe and its relation with high‐energy emission. (© 2016 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)